Improvement of Waste Tire Pyrolysis Oil and Performance Test with Diesel in CI Engine - Islam, M. N.; Nahian, M. R. (Journal of Renewable Energy, 2016)
The standard of living, quality of life, and development of a nation depend on its per capita energy consumption. Global energy supply that mainly depends on fossil fuel is decreasing day by day. It is estimated that the energy demand will be increased five times by the year 2021 from present scenario. Due to the fossil fuel crisis, the development of alternative fuel technologies has drawn more attraction to deliver the replacement of fossil fuel. Pyrolysis is one of the promising alternative fuel technologies which produces valuable oil, char, and gas product from organic waste. Early investigations report that tire pyrolysis oil extracted from vacuum pyrolysis method seemed to have properties similar to diesel fuel. The main concern of this paper is to produce and improve the properties of crude tire pyrolysis oil by desulfurizing, distilling, and utilizing it with diesel in CI engine to analyze the efficiency for various compositions.